COMPETITIVENESS AND POTENTIAL OF SHEEP LIVESTOCK AS SOURCE INCREASING INCOME AND PROVIDER OF MEAT ANIMAL IN NORTH SUMATRA - Sarim Sembiring (UPT Penerbitan Universitas Jember, 2016)
Development of sheep in North Sumatra has a promising future as a source of animal protein provider and increase income. The potential of these animals can be seen from DRCR<1 and the analysis of the feasibility such as N P V +, B / C ratio> 1 and I R R > discount rate shows that sheep deserve to be developed. Development efforts can be done by increasing (1) production and sheep population (2) quality and standards of weight (3) continuity of effort to improve the availability of animal protein and income throughout the year. Development of sheep breeding in accordance with the vision of agribusiness development that sheep can be provider domestic needs and prepare appropriate standards of export markets.